Enantiomeric diarylheptanoids from Ottelia acuminata var. acuminata and their α-glucosidase inhibitory activity - Jia-Ru Zhou; Xin-Yue Hu; Hong-Xing Liu; Yu Zhou; Fei-Fei Xiong; Jian-Jun Zhao; Xing-Ren Li; Gang Xu (Natural Products and Bioprospecting)
Abstract Otteacumienes G–K (1–5), five pairs of enantiomeric diarylheptanoids, along with one undescribed diarylheptanoid glycoside and one new lignan, were isolated from Ottelia acuminata var. acuminata. Compounds 1–5 were identified as five pairs of enantiomers and their structural configurations were determined through a combination of spectroscopic analysis, X-ray crystallography, and ECD calculation. Notably, compound 6 was the first diarylheptanoid glycoside isolated from this aquatic species, and its absolute configuration was unequivocally established through semi-synthesis. Biological evaluation demonstrated that compound 1 exhibited α-glucosidase inhibitory activity, with an inhibition ratio of 38.97% (acarbose as the positive control, inhibition ratio = 13.52%). Graphical abstract